Class Nearly kahler Manifold of W – Projective Curvature Tensor - Ali Khalaf Ali; A. A.Shihab (Tikrit Journal of Pure Science)
The current study deals with new three classes of the  manifold of w – projective curvature tensor. The aim of this paper to calculate differential - geometrical and topological properties closest for new classes , and , through it ,an equivalence relationship was obtained between these classes and one of or more the tensor compounds and the components of curvature tensor and with adjoint G-structure space. Finally, we discover a relationship between ,  ,  with each other.